Beyond The Whiteness of Whiteness : Memoir of a White Mother of Black Sons - Lazarre, Jane (Book collections on Project MUSE., 1996)
Fluid, even ambiguous identity. It is a coming of age that permits a final retelling of family history and family reunion.